2023
DOI: 10.1113/ep091275
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb hyperthermia augments functional hyperaemia during small muscle mass exercise similarly in trained elderly and young humans

Abstract: New Findings What is the central question of the study? Ageing is postulated to lead to underperfusion of human limb tissues during passive and exertional hyperthermia, but findings to date have been equivocal. Thus, does age have an independent adverse effect on local haemodynamics during passive single‐leg hyperthermia, single‐leg knee‐extensor exercise and their combination? What is the main finding and its importance? Local hyperthermia increased leg blood flow over three‐fold and had an additive effect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
(143 reference statements)
1
0
0
Order By: Relevance
“…In this study, all three modalities of upper‐leg heating – WTH, QH and PQH – evoked sustained 1.4−2‐fold increases in CFA blood flow (Figure 3 ). In line with previous studies, local hyperthermia‐induced increases in leg tissue perfusion, assessed via CFA blood flow, occurred in relation to increases in local tissue temperature (Chiesa et al., 2016 ; Koch Esteves et al., 2021 , 2023 ). A previous study from our laboratory revealed that the magnitude of hyperaemia was associated with the volume of the heated limb segment, with whole‐leg heating evoking the largest degree of hyperaemia, proportionally followed by upper‐ and lower‐leg heating, respectively (Koch Esteves et al., 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, all three modalities of upper‐leg heating – WTH, QH and PQH – evoked sustained 1.4−2‐fold increases in CFA blood flow (Figure 3 ). In line with previous studies, local hyperthermia‐induced increases in leg tissue perfusion, assessed via CFA blood flow, occurred in relation to increases in local tissue temperature (Chiesa et al., 2016 ; Koch Esteves et al., 2021 , 2023 ). A previous study from our laboratory revealed that the magnitude of hyperaemia was associated with the volume of the heated limb segment, with whole‐leg heating evoking the largest degree of hyperaemia, proportionally followed by upper‐ and lower‐leg heating, respectively (Koch Esteves et al., 2021 ).…”
Section: Discussionsupporting
confidence: 88%